Investigation on pharmacokinetics, tissue distribution and excretion of 1-triacontanol in rats by gas chromatography-tandem mass spectrometry (GC-MS/MS). (January 2015) - Wang, Chunfeng; Fan, Ali; Deng, Shuhua; Gao, Wenchao; Zhang, Wei; Yang, Wei; Zhu, Xiaojie; Lu, Yang; Chen, Xijing
Abstract 1. 1-Triacontanol (TA) recently shows promising anti-tumor activity. The present study was aimed to develop a sensitive gas chromatography-tandem mass spectrometry method to explore the pharmacokinetic profiles, distribution and excretion of TA in Sprague-Dawley rats after oral administration of TA. Chromatography separation was performed on a HP-5MS column. 1-Octacosanal was used as the internal standard (IS). Quantification of TA and IS was carried out at m/z 495.6 → 97.0 and m/z 467.5 → 97.0, respectively, in positive electron ionization and multiple reaction monitoring mode. The pharmacokinetic parameters were calculated by non-compartmental analysis. 2. The area under concentration-time curve AUC0–6 h and AUC0–∞ for TA at 60 mg/kg were 87.737±13.574 and 93.617±17.62, respectively. The mean residence time was 3.25 ± 0.17 h. In addition, the elimination half-lives (t1/2) were (2.37±1.23, 1.27±0.49, 2.07±0.93) h after single oral administration of 30, 60 and 120 mg/kg of TA. After oral administration, TA was extensively distributed in stomach and intestine. The majority of TA excreted via feces, and its accumulative excretion ratio during the period of 72 h was 26.68 ± 7.14%, but only 0.0023 ± 0.0015% and 0.0027 ± 0.0006% for urines and bile, respectively. The absolute bioavailability (F, %) of TA was about 2.0%.